Stabilization mechanism and remediation effectiveness of Pb and cd in agricultural soil using nonmetallic minerals - Fei Liao; Kaibin Fu; Wei Zhang; Han Song; Yunlong Kong; Zhongcheng Wang; Jun Tang (Scientific Reports)
Abstract Soil contaminated by Pb and Cd has aroused worldwide concern due to the environmental hazards they pose. The effects, mechanisms, and evaluation of Pb and Cd contaminated agricultural soil remediation by nonmetallic minerals are still poorly understood. In this study, solidification/stabilization experiments were used to screen nonmetallic mineral materials and optimize their dosages. Stabilization mechanisms of Pb and Cd by nonmetallic mineral materials were investigated by adsorption kinetics, X-ray diffraction spectroscopy, and Fourier transform infrared spectroscopy. The effectiveness of soil remediation was further confirmed through a pot experiment with pak choi (Brassica rapa L. subsp. chinensis), an important non-heading leafy vegetable. Results demonstrated that the SL composite (composed of 2.5% sepiolite and 1.5% limestone, with a total dosage of 4.0%) exhibits the optimal stabilization effect on soil contaminated with Pb and Cd. In soils with low, medium, and high contamination levels, SL reduced the bioavailability of Pb by 97.97%, 96.78%, and 95.82%, and the bioavailability of Cd by 92.96%, 91.76%, and 91.02%, respectively. SL surfaces are rich in hydroxyl (–OH) and carbonate (CO32−) groups, enabling binding with Pb and Cd ions to form hydroxide and carbonate precipitates. Such interactions suggest that chemical adsorption primarily drives Pb and Cd ion stabilization, reducing their bioavailability in soil. Pak choi grown in SL-remediated soil exhibited Pb and Cd contents compliant with China’s food safety standards. These findings further validate the bioavailability reduction rate as a suitable metric for evaluating the remediation effectiveness of heavy metal pollution in agricultural soils. This study provides a new strategy for evaluating the remediation efficiency of heavy metal-contaminated agricultural soil.